Epoxide and cyclic carbonate with diisononyl succinate backbone as phthalate-free plasticizers. Issue 8 (24th February 2016) - Polyakov, Mykola; Schäffner, Benjamin; Kruse, Daniela; Martin, Andreas; Köckritz, Angela
Graphical abstract: Highlights: Epoxidized diisononyl maleate and carbonylated diisononyl tartrate were synthezised. The synthesis of the cyclic carbonate was scaled up to multi-decagrams. The performance of the novel materials as phthalate-free plasticizers was tested. The materials show plasticizing properties comparable to phthalate-based plasticizers. Abstract: Candidates for new phthalate-free plasticizers are synthesized based on epoxidized diisononyl maleate and carbonylated diisononyl tartrate. Although the carbonation of epoxidized diisononyl maleate with CO2 failed, the cyclic carbonate was synthesized successfully using triphosgene as carbonylation agent of the respective tartrate. The performance of the synthesized materials as plasticizer was analyzed under standard conditions as plastisols. Results showed potential for the epoxidized maleate and carbonylated derivative to be developed into phthalate free-plasticizers.